(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article examines comprehensive strategies for poverty reduction, emphasizing the importance of addressing the multidimensional aspects of poverty. It highlights key interventions such as education and skill development, employment creation, social protection policies, infrastructure development, gender equality, and community participation. By adopting a holistic approach, societies can effectively tackle poverty and create opportunities for sustainable development and inclusive growth.